UJI AKTIVITAS ANTIBAKTERI EKSTRAK DAUN GARCINIA MICROCARPA TERHADAP 11 BAKTERI PATOGEN MANUSIA - Ningsih, Yozi Fiedya; Arbain, Dayar; Bakhtiar, Amri (Ensiklopedia of Journal, 2025)
Abstract: Infections caused by pathogenic bacteria remain a significant global health issue, particularly with the growing incidence of antimicrobial resistance. Therefore, the search for new antibacterial sources from medicinal plants has become a promising alternative. Garcinia microcarpa, a species belonging to the Garcinia genus, is known that Garcinia contains bioactive compounds such as xanthones, flavonoids, and tannins, which have potential antibacterial properties. This study aimed to evaluate the antibacterial activity of Garcinia microcarpa leaf extract against 11 human pathogenic bacteria, namely Staphylococcus aureus, Streptococcus mutans, Staphylococcus epidermidis, Enterococcus faecalis, Micrococcus luteus, Bacillus subtilis, Pseudomonas aeruginosa, Vibrio cholerae, Escherichia coli, Salmonella typhii, and Salmonella typhosa. Leaf extraction was performed using the maceration method with methanol as the solvent. Antibacterial activity was assessed using the disk diffusion method. The results showed that Garcinia microcarpa leaf extract exhibited antibacterial activity with varying inhibition zones against the tested bacteria. The highest activity was observed against E. coli and S. epidermidis, with inhibition zone diameters of 13.8 ± 1 mm and 13.0 ± 0.3 mm, respectively, at a concentration of 1 mg/disk. These findings suggest that Garcinia microcarpa has potential as a natural source of antibacterial compounds. Further studies are needed for fractionation, isolation of active compounds, and bioactivity testing.Keywords: Garcinia microcarpa, extract, antibacterial activity.